Genetic syndromes associated with overgrowth in childhood - Ko, Jung Min (The Korean Society of Pediatric Endocrinology, 2013)
Overgrowth syndromes comprise a diverse group of conditions with unique clinical, behavioral and molecular genetic features. While considerable overlap in presentation sometimes exists, advances in identification of the precise etiology of specific overgrowth disorders continue to improve clinicians' ability to make an accurate diagnosis. Among them, this paper introduces two classic genetic overgrowth syndromes: Sotos syndrome and Beckwith-Wiedemann syndrome. Historically, the diagnosis was based entirely on clinical findings. However, it is now understood that Sotos syndrome is caused by a variety of molecular genetic alterations resulting in haploinsufficiency of the NSD1 gene at chromosome 5q35 and that Beckwith-Wiedemann syndrome is caused by heterogeneous abnormalities in the imprinting of a number of growth regulatory genes within chromosome 11p15 in the majority of cases. Interestingly, the 11p15 imprinting region is also associated with Russell-Silver syndrome which is a typical growth retardation syndrome. Opposite epigenetic alterations in 11p15 result in opposite clinical features shown in Beckwith-Wiedemann syndrome and Russell-Silver syndrome. Although the exact functions of the causing genes have not yet been completely understood, these overgrowth syndromes can be good models to clarify the complex basis of human growth and help to develop better-directed therapies in the future.